PENGARUH SELF-ESTEEM, EFIKASI DIRI DAN ADVERSITY QUOTIENT TERHADAP RESILIENSI KERJA PT. ORIFLAME INDONESIA - Ervin Mardalena; Noviansyah; Darman Syafe’i; Palupi Indah Sari (Fakultas Ekonomi dan Bisnis Universitas Baturaja, 2026)
Amidst the increasingly competitive landscape of the digital era, organizations require highly adaptable human resources capable of navigating dynamic workplace challenges. Consequently, work resilience has emerged as a critical core competency for professionals. This study aims to examine the impact of self-esteem, self-efficacy, and adversity quotient on the work resilience of independent supervisors and consultants at PT Oriflame Indonesia in South Jakarta. Employing a descriptive quantitative methodology, data was gathered through Likert-scale questionnaires administered to 103 respondents selected via saturated sampling. The collected data was subsequently analyzed using multiple linear regression with IBM SPSS